One level up: abnormal proteolytic regulation of IGF activity plays a role in human pathophysiology - Jesús Argente; Julie A Chowen; Luis A Pérez‐Jurado; Jan Frystyk; Claus Oxvig (EMBO Molecular Medicine)
Abstract The discovery of a mutation in a specific gene can be very important for determining the pathophysiology underlying the disease of a patient and may also help to decide the best treatment protocol on an individual basis. However, sometimes the discovery of mutations in new proteins advances our comprehension in a more widespread manner. The growth hormone (GH)/insulin‐like growth factor (IGF)‐1 axis is fundamental for systemic growth, but is also involved in many other important processes. Our understanding of this system in physiology and pathophysiology has advanced throughout the years with each discovery of mutations in members of this axis. This review focuses on the most recent discovery: mutations in the metalloproteinase pregnancy‐associated plasma protein‐A2 (PAPP‐A2), one of the proteases involved in liberating IGF‐1 from the complexes in which it circulates, in patients with delayed growth failure. We also discuss the advances in the stanniocalcins (STC1 and STC2), proteins that modulate PAPP‐A2, as well as PAPP‐A. These new advances not only bring us one step closer to understanding the strict spatial and temporal control of this axis in systemic growth and maturation, but also highlight possible therapeutic targets when this system goes awry.